Flying Capacitor Double Dual Boost DC-DC Converter - Pedro Martín García-Vite; Julio C. Rosas-Caro; Josué Francisco Rebullosa-Castillo; Manuel Alejandro García-Perales; Jesús Eduardo Pedraza-Barrón; Brenda Lizeth Reyes-García (My University, 2024)
This article presents a detailed analysis of a previously introduced boost converter based on cascaded capacitor connections. The analyzed converter maintains the same voltage gain as its conventional double-boost converter counterpart. The main advantage of the redesigned converter is that it requires smaller capacitors, rated to a lower voltage, due to the cascaded connection. This makes it suitable for various applications, including distributed generation and microgrids. This paper conducts the mathematical modeling of the converter with large signal models and the equilibrium operation in continuous conduction mode, employed to implement a control scheme. Even though the individual capacitor voltage ripple reaches high values, for voltage gains above five, the output voltage ripple is lower compared with that of other converters. The analysis also includes a comparative study with the conventional double dual boost converter. Simulations assess the proposed topology’s ability to effectively minimize the switching ripple in the output voltage, even with smaller capacitors. Finally, experimental results are also provided to confirm the functionality of the proposed converters under various operational conditions, which confirm its suitability for low-voltage generator applications.